The evaluation and testing of mobile ITS interventions on speed compliance in the minibus taxi industry of South Africa - Akoku Ebot Eno Akpa, Nelson (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.